p=zx,q=zy
Let f(x,y,z,p,q)=yp2−2(z+xp+yq)
So that
fx=−2p,fy=p2−2q,fz=−2,fp=2py−2x,fq=−2y
Then we use Charpits method:
dx/fp=dy/fq=dz/(pfp+qfq)=−dp/(fx+pfz)=−dq/(fy+qfz)
Then,putting all the values and then equating the second and the fourth terms,
we have p=c/(y*2) and from −dp/(fx+pfz)=−dq/(fy+qfz)
gives pq=p3/(12+a), where a and c are constants.
Finally get next:
dz=(c/y2)dx+((c2−2y3z−2cxy2)/(2y4))*dy.
we have the equation :
dz=(c/y2)dx+((c2−2y3z−2cxy2)/(2y4))dy
let's open the brackets on the right side of the equation and then
move to the left part of the expression written to the right, so we have:
dz+(2y3 z)dy/(2y4)=(с/у2)dx+ c2dy/(2y4)- 2cxydy/(2y4)
Then we get: dz+(zdy)/y=cdx/y2+c2dy/2y4-cxdy/y3
Now we multiply all expressions by 2y, after that we get
2(ydz+zdy)=(c2/y3)dy+2c(ydx−xdy)/(y2)
⟹2(ydz+zdy)=(c2/y3)dy+2c(ydx−xdy)/(y2)
(ydz+zdy) is a differential of yz (differential of product)
(ydx−xdy)/(y2) is a differential of x/y
So we have: 2d(zy)=(c2/y3)dy+2cd(x/y)
⟹2d(zy)=(c2/y3)dy+2cd(x/y)
and then we integrate this equation and in result we have:
⟹2zy=−c2/(2y2)+2cx/y+c1, where c1 is a constant.
Comments
Leave a comment